Illusory consensus Bolingbroke and the polemical response to Walpole, 1730-1737 - Pettit, Alexander 1958- (Univ. of Delaware Press [u.a.], 1997)
Alexander Pettit analyzes the formation of and the reaction against the notion of a unified opposition to England's de facto prime minister Sir Robert Walpole (1676-1745), the "great man" of Scriblerian satire who was reviled throughout the 1730s for his hostility to the belles lettres, his alleged disregard of the royal prerogative, and his concentration of power in an oligarchy of parliamentary "placemen." The discussion draws extensively on ephemeral plays, sermons, pamphlets, and newspapers that in their own day were regarded as significant contributions to the political debate. Pettit shows that the myth of coherent anti-Walpoleanism was promoted vigorously by Henry St. John, Viscount Bolingbroke (1678-1751), cofounder of the popular opposition weekly, the Craftsman. But Pettit argues that much of the anti-Walpole literature of the 1730s responds anxiously to Bolingbroke's prescriptive theorizing and questions or criticizes the terms of his appeals to consensus. The opposition was fundamentally in disagreement about how to formulate its objection to modern government. Bolingbroke's reductive fantasy of the opposition has been regarded charitably by modern commentators, most of whom have chosen to regard the "print-wars" as the occasion for Bolingbroke's major political treatises or as background to the satire of his friends, the Scriblerians. This emphasis on a small and interconnected group of writers and sources, however, has caused scholars to neglect the opposition's diversity and its lack of coherence.
Keywords: Bolingbroke, Henry St. John <Viscount, 1678-1751>; Walpole, Horace <1717-1797>; Walpole, Horace -- 1717-1797; Bolingbroke, Henry St. John -- 1678-1751; Geschichte 1830-1737; Geschichte 1730-1737; Politik; Consensus (Social sciences); Polemics; Großbritannien; Great Britain -- Politics and government -- 1727-1760